Peran Zakat, Infak, Sedekah, dan Wakaf dalam Mendukung Pencapaian Sustainable Development Goals (SDGs) - M. Rifqi Choirul Anwar; Nafaatul Ummah; Nida Alfina Nihlah; Mohammad Soleh (IQTISODINA, 2025)
This study aims to analyze the role of zakat, infaq, sedekah, and waqf (ZISWAF) in supporting the achievement of the Sustainable Development Goals (SDGs). ZISWAF is an Islamic social financial instrument with significant potential for promoting sustainable development, but its utilization remains suboptimal and not fully integrated with the SDGs agenda. This study used a qualitative approach with a literature review method through a review of scientific journals, books, and other relevant literature. The results indicate that ZISWAF plays a significant role in poverty reduction, improving social welfare, and empowering the community's economy, particularly through productive zakat, support for education and health, and the management of productive waqf. With professional, transparent management, and integration with development policies, ZISWAF has the potential to become a strategic instrument in supporting inclusive and sustainable development in accordance with the SDGs.